Performance. The Secrets of successful Behaviour - Stuart-Kotze R. Robin (London, Prentice Hall, 2006)
We all do hundreds of different things at work each day, but which ONES REALLY MAKE A DIFFERENCE?AND IF YOU'RE MANAGING OTHER PEOPLE, HOW DO YOU IMPROVE THEIR PERFORMANCE?Behaviour is what drives performance. Personality is not the issue. Definitive scientific research shows that less than 10% of the variance in a person's behaviour is explained by personality.Behaviour is the actions you take and the decisions you make. You can control these things; you can decide what to do and when to do it. You can see these things, and you can measure them. And because you can decide what to do in any situation you can determine, control and most importantly, improve, your performance. In fact, performance is all about doing the right thing at the right time.This incisive book shows you how to look critically at your current behaviour, recognise what you need to do differently and how to consciously improve your behaviour to meet the changing requirements of your job with top-level performance:1. Recognise the actions that accelerate performance- and do more of them.2. Learn to identify performance blocking behaviour- and stop it.3. Accept that the people who best know how to e"=~;e ce^ormance are those doing the job -and ask them, don't tell them about improvements.These are the secrets of successful behaviour, and this is Behaviour Kinetics. The difference starts here.What appeals first and foremost about the book в its sheer readability. The content is compelling and one just enjoys turning the pages to see what comes next. How many management booksChrts Tomkinson. Former Director of Rothmans% improving business performance the top. Finally, a book that helps you directng, MD, Britax Childcare Europe